Preparation and Support of Patients through the Transplant Process: Understanding the Recipients' Perspectives - Oliver Mauthner; Enza De Luca; Jennifer Poole; Mena Gewarges; Susan E. Abbey; Margrit Shildrick; Heather Ross (Hindawi Limited, 2012)
Preparation for heart transplant commonly includes booklets, instructional videos, personalized teaching sessions, and mentorship. This paper explores heart transplant recipients' thoughts on their preparation and support through the transplant process. Twenty-five interviews were audio-/videotaped capturing voice and body language and transcribed verbatim. Coding addressed language, bodily gesture, volume, and tone in keeping with our visual methodology. Recipients reported that only someone who had a transplant truly understands the experience. As participants face illness and life-altering experiences, maintaining a positive attitude and hope is essential to coping well. Healthcare professionals provide ongoing care and reassurance about recipients' medical status. Mentors, family members, and close friends play vital roles in supporting recipients. Participants reported that only heart transplant recipients understood the experience, the hope, and ultimately the suffering associated with living with another persons' heart. Attention needs to be focused not solely on the use of teaching modalities, but also on the development of innovative support networks. This will promote patient and caregiver engagement in self-management. Enhancing clinicians' knowledge of the existential aspects of transplantation will provide them with a nuanced understanding of the patients' experience, which will ultimately enhance their ability to better prepare and support patients and their caregivers.